Perbandingan Hasil Belajar Ekonomi Model Pembelajaran ETH, GQGA dan TGT - Zeyca Wilantini; Yon Rizal; Edy Purnomo (JEE (Jurnal Edukasi Ekobis), 2017)
The purpose of this research was to know the difference of learning outcomes of student analysis which learning using cooperative model type ETH, GQGA and TGT on Economic study learning outcomes. The method used in this research was quasi experiment with comparative approach design Post Test Only, Non Equivalent Control Group Design. The population in this study is as many as 7 classes with the number of 291 students and the sample used as much as 3 classes with the number of 124 students determined through cluster random sampling. Data collection techniques used tests. Hypothesis testing using one way street variance analysis and t-dunnet long testing. Based on analysis of the data, it obtained the results: There is a difference of learning outcomes among students whose learning using cooperative model type ETH, GQGA and TGT on Economic study learning outcomes.Tujuan penelitian ini untuk mengetahui perbedaan rata-rata hasil belajar siswa yang pembelajarannya menggunakan model pembelajaran kooperatif tipe ETH, GQGA, dan TGT pada mata pelajaran Ekonomi. Metode penelitian yang digunakan adalah eksperimen semu dengan pendekatan komparatif desain Post Test Only, Non Equivalent Control Group Design. Populasi dalam penelitian ini sebanyak 7 kelas dengan jumlah 291 siswa dan sampel yang digunakan sebanyak 3 kelas dengan jumlah 124 siswa yang ditentukan melalui cluster random sampling. Teknik pengumpulan data melalui tes. Pengujian hipotesis menggunakan analisis varians satu jalan dan uji lanjut t-dunnet. Berdasarkan analisis data diperoleh hasil: Ada perbedaan rata-rata hasil belajar siswa yang pembelajarannya menggunakan model pembelajaran kooperatif tipe ETH, GQGA, dan TGT pada mata pelajaran Ekonomi.Kata kunci: Ekonomi, Hasil Belajar, ETH, GQGA, TGT